Quality of Life of People with HIV/AIDS in Iran: A Systematic Review and Meta-Analysis - Mohammad Reza MALEKI; Naser DERAKHSHANI; Saber AZAMI-AGHDASH; Mehran NADERI; Mahdi NIKOOMANESH (Tehran University of Medical Sciences, 2020)
Background: Assessing the quality of life in HIV/AIDS patients is of great importance not only for evaluating the effect of the disease, but also to measure the impact of the interventions in order to improve their quality of life in clinical researches. Therefore, this study aimed to systematically review the quality of life of HIV/AIDS patients in Iran. Methods: In this systematic review and meta-analysis, the literature search using the related chain of keywords was conducted from 1 Jan 1987 to 30 Apr 2019 in PubMed, Scopus, Web of Science, Embase, Iranian Scientific Information Database (SID), and Magiran. Moreover, hand search of the key journals and the gray literature was performed. The meta-analysis was performed by CMA2 software. Results: Out of the 1576 retrieved records, eight studies met the inclusion criteria. The average age of the patients was 37.15 ± 9.46 years. The average score of quality of life before and after sensitivity analysis was (39.13 [28.36-49.901 95% CI P>0.000] vs. 49.05 [46.31-51.79 95% CI P>0.000]). Moreover, the average score of quality of life was respectively 38.86±3.83 vs. 40±6.37 among married compared with single patients, 56.33±4.67 vs. 43.64±1.94 for employment vs. unemployment status. While quality of life was measured in terms of education level, the score was 29.59±9.34 vs. 41.65±4.45 in the individuals with primary school versus academic education. Conclusion: The QOL score of the HIV/AIDS patients in Iran was significantly low. Therefore, the study highlights the importance of strengthening efforts to undertake necessary investigations in order to provide adequate health insurance, extensive and affordable welfare services, and more appropriate social and mental supports in order to improve the quality of life of the individuals with HIV/AIDS in Iran.